The Sangurimas, a Polemic Narrative Work (Castilla. Estudios de Literatura, 2011)
In the thirties, the Ecuadorian literature experiments an important change in its themes as well as in its narrative structure. When romanticism was in vogue in the 19th Century, Two Ecuadorian writers already call our attention powerfully: Juan Montalvo for the purity of his prose, the spirited aspect of his themes and because he was a precursor of modernism. Juan León Mera, on the other hand, was highly regarded for his excellent narrative work, especially for following the norms dictated by the European masters. In the 20th Century, in the Hispanic American vanguard era two writers stand out: Pablo Palacio when he breaks social taboos and De la Cuadra one of the stronger initiators of magic realism in South America. Los Sangurimas, by José de la Cuadra, is a narrative work that describes the outrageous behavior of a dynasty. The people –family and neighbors- are submitted to one man’ hegemonic power, abuses and repression are intolerable. Los Sangurimas denounce and, at the same time, affirms the cruelty of caciquismo which acted in any village, large or small, becoming an endemic characteristic of the 19th and 20th Centuries in Latin America. Likewise, in this work we find analogies in the structure, the themes, and the characters which are introduced by the geography. All this is done, with the purpose to emphasize and to analyze the improbable, the mythic and the legendary.